Contraceptive behaviour of Czech and Romanian women: comparison of representative national samples - Gregorová, Pavlína; Weiss, Petr; Unzeitig, Vít; Cibula, David (European journal of obstetrics, gynecology, and reproductive biology, 2011)
OBJECTIVE: To investigate the contraceptive behaviour of Czech and Romanian women and their attitudes towards different forms of contraception. STUDY DESIGN: Anonymous questionnaire research among 1011 Czech and 1001 Romanian women between 15 and 50 years of age. The samples were representative of both the Czech and Romanian female populations with respect to age, education and the size of their place of residence. RESULTS: The majority of women use contraception when in a stable sexual relationship. We found a higher percentage of women using contraception among Czech women. Romanian women more often use less reliable methods in a stable relationship, and condoms. Czech women use hormonal contraception much more. Women in the Czech Republic would more often agree to use a condom and, in particular, to use hormonal and intrauterine contraception. More Romanian women than Czech women prefer the method of infertile days. The use of contraception is influenced by the factors of age, education and size of the place of residence. CONCLUSION: The majority of Czech and Romanian women protect themselves against unwanted pregnancy. Czech women are more frequent users of contraceptives in general and, in particular, of hormonal contraception. Romanian women tend to use less reliable methods of contraception but on the other hand, they more often use condoms as a means of protection.
Keywords: Romania; dospělí; antikoncepční chování; těhotenství; Humans; lidé středního věku; Middle Aged; Health Knowledge, Attitudes, Practice; Czech Republic; zdraví - znalosti, postoje, praxe; Česká republika; Adult; Contraception; Adolescent; ženské pohlaví; Contraception Behavior; Rumunsko; kondomy; lidé; mladiství; Pregnancy; Condoms; antikoncepce; Female